Pengaruh Media Sosial Tiktok Terhadap Tingkat Partisipasi Politik Mahasiswa Generasi Z di UPN Veteran Jakarta - Ichwanusafa, Rifki; Aji, Muhammad Prakoso (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In its early days, TikTok, once considered as moral disruptor to the nation, has now envolved into a social media platform that significantly influences the social life of the community. The ease of getting on the â€œFor Your Pageâ€ (FYP) or going viral on TikTok is now interwind with the social and political life of society This research aims to understand the influence of TikTok on the level of political participation among Generation Z students at UPN â€œVeteranâ€ Jakarta who reside in DKI Jakarta, as well as to determined the significance of this influence. This study employs a mix-methods approach, utilizing both quantitative and qualitative methods. It involves 100 respondents who are students a UPN â€œVeteranâ€ Jakarta residing in DKI Jakarta, selected through non-probability purposive sampling from a total population of 5701 students. The results of this research indicate the following: First, based on both quantitative and qualitative data, TikTok effectively captures the attention of Generation Z students at UPN â€œVeteranâ€ Jakarta, encouraging the to actively participate in political activities. Second, the influence exerted by TikTok on the level of political participation of Generation Z students at UPN â€œVeteranâ€ Jakarta in DKI Jakarta is at 49.4%. Third, based on quantitative data, Generation Z students at UPN â€œVeteranâ€ Jakarta show interest and active participation in political activities on TikTok. Fourth, despite being interested in political campaign content on TikTok, Generatin Z students at UPN â€œVeteranâ€ Jakarta are not inclined to join political parties or campaign teams, as indicated by quantitative data. Fifth, UPN â€œVeteranâ€ Jakarta students agree that TikTok influence their political choices for 2024 elections. The results of both quantitative and qualitatives research mutually support each other, indicating consistency in the views of Generation Z students at UPN â€œVeteranâ€ Jakarta regarding the influence of TikTok on the level of political participation. Â